Silver nanoparticles with high loading capacity of amphotericin B: Characterization, bactericidal and antifungal effects - Leonhard, Victoria (2017)
The purpose of this study was to evaluate the most appropriate conditions to generate silver nanoparticles (AgNPs) loaded with a potent antimycotic drug like amphotericin B (AmB), characterize the physicochemical properties, and to evaluate the cytotoxic effect and biological activity of these new nanostructures as a potential nanocarrier for hydrophobic drugs. It was determined that the optimal molar ratio between Ag and AmB is 1/1 given the uniformity of size around 170 nm of the nanoparticles generated as well as their strongly negative ζ potential of -35 mV, a condition that favors repulsions between AgNPs and inhibiting their aggregation. In this condition, only 0.8 mg.mL-1 of Ag is needed to solubilize 5 mg.mL-1 of AmB, a concentration currently used in commercial formulations. It is important to emphasize that the loading capacity (w/w) of this nanostructure is much higher than that of micellar and liposomal formulations. These AgNP-AmB nanoparticles retain both the bactericidal effect of silver and the cytotoxic and antifungal effect of AmB. However, it was shown that these nanoparticles are spontaneously associated with plasma lipoproteins (LDL and HDL), inhibiting their cytotoxic effects on red blood cells and on at least two cell lines, Vero and H1299 and slightly reducing its bactericidal effect on P. aeruginosa. In contrast, the antifungal effect of the formulation is maintained and is even higher than that when the nanoparticle is not associated with lipoproteins, indicating that this association is of the reversible type. The characterization of these nanoparticles is discussed as a potential new model formulation able to improve the antifungal therapeutic efficiency of AmB.